Madrasah Diniyah and Ma'had Al-Jami'ah-Based Religious Moderation Policy in State Islamic University in Indonesia - Naim, Ngainun; Abad Badruzaman; Izzatul Amalina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article seeks to elaborate the ma’had al-jami’ah-based religious moderation policy at UIN Sayyid Ali Rahmatullah Tulungagung. This issue is interesting because religious moderation is a government policy that must be implemented by government institutions, including Islamic religious universities. The problem is that there are no nationally formal technical-operational guidelines for implementation so each tertiary institution has an interpretation for making policies to strengthen religious moderation by their respective contexts and considerations. The current study used in this article is qualitative with data mining techniques through interviews, observation, and documentation. The data that has been obtained is then analyzed using the Miles, Huberman, and Saldańa model which divides the stages of data analysis into data condensation, data presentation, and conclusion. This article argues that UIN Sayyid Ali Rahmatullah made interesting policies for religious moderation in the form of madrasah diniyah and ma’had al-jami’ah learning policies. Madrasah diniyah and ma’had al-jami’ah are designed not only as an activity to provide religious knowledge to students but also as a strategy for internalizing religious moderation and prevention of radicalism ideology.